Improving the learning outcome of clinical training for students in veterinary dermatology service - Schjærf, Mette (Improving University Science Teaching and Learning, 2023)
In general, veterinary master students have limited training in clinical dermatology at their general clinical course program. This is a challenge as dermatology is a highly frequent area of presentation in veterinary practice. In fact, around 20-30% of all small animal consultations in general practice is rooted in a skin problem (Hill, 2006). At Dermatology Service at the University Hospital of Companion Animals, UCPH, the students often have only one or two days on clinical service as part of their general hospital clinical course. Often the students are perplexed about their role and unsure of the specific Intended Learning Outcomes (ILOs) and do not have enough time to become familiar with practicals during this narrow time frame. This calls for the students to take full advantage of the time and use it in the most optimal way to gain as much knowledge and hands-on experience in dermatology as possible. Thus, implementing a way to emphasize the expectations, including making practicalities more clear as well as having concise ILOs for the students before the rotation starts is key for a more optimal learning outcome, given the short time.